TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PEMBUNUHAN BERENCANA - Nopiana Mozin (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
This study aims to determine the application of the elements of the crime of premeditated murder under Article 340 of the criminal code in Decision No : W20.U1/25 / AT.05.02/12/2019 and to find out the legal considerations of the panel of judges in the imposition of penalties against perpetrators of premeditated murder in the decision No. W20.U1/25 / AT.05.02/12/2019.The method used in this study is the technique of data collection by way of research study of documents conducted in the Gorontalo District Court and reading literature and other reading sources as well as interview techniques in which the authors conduct direct questioning to the parties concerned in this case Gorontalo District Court judges, prosecutors and legal experts concerning the object research. The results of this study showed that the application of elements of the crime of premeditated murder law and Decision No: W20.U1/25 / AT.05.02/12/2019 is accurate.the public prosecutor uses the indictment of the first indictment primair Article 340 of KUHP ,indictment subsidiair 338 of KUHP indictment more subsidair 351 paragraph(3) of KUHP and the second indictment 285 of KUHP